An update on prosthetic joint infection for UK trainees - Sabah, SA; Shearman, AD; Alvand, A (Elsevier, 2021)
Prosthetic joint infection (PJI) is where a joint that has been replaced with an orthopaedic implant becomes infected. PJI is given special consideration because of difficulties in treatment and the potential for life- and limb-changing sequelae for patients. Management of PJI requires collaboration between multiple specialists and is best managed within a multidisciplinary team. This article provides an overview on the diagnosis and treatment of PJI. We have described clinical prediction rules used to aid diagnosis in challenging cases. We have outlined first-line treatment options (such as debridement, antibiotics and implant retention (DAIR) procedures, single-stage and two-stage revision surgery), and second-line treatments (including chronic antibiotic suppression and salvage procedures).